2021
DOI: 10.1617/s11527-021-01745-3
|View full text |Cite
|
Sign up to set email alerts
|

Deformational behavior and damage mechanism of R-UHPFRC beam subjected to fatigue loading

Abstract: The fatigue behavior of a reinforced UHPFRC (Ultra High Performance Fiber Reinforced Cementitious composite) T-shaped beam under four-point bending is investigated. The beam was subjected to a fatigue loading range equal to 49% of the static resistance and failed after 0.88 million cycles. It was instrumented with extensometers, strain gauges and distributed fiber optic sensors for strain monitoring. The fatigue process consists of three stages: with rapid, stable and again rapid growth of strains during 10%, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Three types of beams with T-cross section were tested: Type I with a single Ø20 mm steel rebar; Type II with a single Ø34 mm rebar and Type III with Ø20 mm Sawicki and Brühwiler Int J Concr Struct Mater (2024) 18:6 longitudinal rebar and Ø6 mm Ω shaped stirrups. Their dimensions are specified in Fig.…”
Section: Setupmentioning
confidence: 99%
“…Three types of beams with T-cross section were tested: Type I with a single Ø20 mm steel rebar; Type II with a single Ø34 mm rebar and Type III with Ø20 mm Sawicki and Brühwiler Int J Concr Struct Mater (2024) 18:6 longitudinal rebar and Ø6 mm Ω shaped stirrups. Their dimensions are specified in Fig.…”
Section: Setupmentioning
confidence: 99%
“…Combined with the electric power calculation formula, the excitation coil's input power P in and the millivoltmeter's output power P o as the load can be calculated, respectively. The results are shown in Equations ( 8) and (9). The transmission efficiency can be obtained as shown in Equation (10).…”
Section: Theorymentioning
confidence: 99%
“…The test is carried out by pasting electronic strain gauges or embedded sensors, and then converting the stress. Sawicki [9] successfully identified the stress of rebars by using strain gauges installed on rebars and distributed optical fiber sensors for strain detection. However, this method is susceptible to temperature and has low durability.…”
Section: Introductionmentioning
confidence: 99%
“…This selected range corresponds to 25% of the flexural strength of the retrofitted specimen, as determined from the moment-curvature analysis. Prior research on the fatigue testing of reinforced UHPC beams has indicated rapid stiffness degradation when subjected to a loading range approximating 50% of the static strength [31,32]. Contrary to this, this study opted for a loading range equivalent to 25% of the flexural strength of the specimen, aiming to monitor stiffness degradation under repeated loading.…”
Section: Cyclic Testingmentioning
confidence: 99%